1996
DOI: 10.1111/j.1472-765x.1996.tb01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a commercial biochemical kit and an oligonucleotide probe for identification of environmental isolates of Vibrio vulnificus

Abstract: Methods for the identification and isolation of environmental isolates of Vibrio vulnificus were evaluated. Alkaline peptone water supplemented with polymyxin B and colistin-polymyxin B-cellobiose agar were employed for the isolation of suspected V. vulnificus from water, sediment and shellfish samples. When comparing the identification of putative V. vulnificus obtained with the API 20E assay and an oligonucleotide probe, 29 API 20E profiles were obtained with only four profiles (representing 20 isolates) rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Given the fact that previous reports have already concluded that the use of API 20 E is inadequate for the identification of V. vulnificus (6), only the API 20 NE system was used in this study. API 20 NE strips were inoculated and processed following the manufacturer's recommendations, and the results were analyzed by using Apilab software, version 3.2.2.…”
Section: Methodsmentioning
confidence: 99%
“…Given the fact that previous reports have already concluded that the use of API 20 E is inadequate for the identification of V. vulnificus (6), only the API 20 NE system was used in this study. API 20 NE strips were inoculated and processed following the manufacturer's recommendations, and the results were analyzed by using Apilab software, version 3.2.2.…”
Section: Methodsmentioning
confidence: 99%
“…The few studies conducted have, however, revealed the presence of V. parahaemolyticus and V. vulnificus (3,9,14).…”
mentioning
confidence: 99%
“…Later, CPC agar was modified (mCPC) by reducing the concentration of colistin (33), which improved the recovery and isolation of V. vulnificus from environmental sources. Recently, a new modification of CPC agar has been described (16).To identify presumptive V. vulnificus recovered from these media, probes based on the cytolysin gene of V. vulnificus have been developed (11,25,37). The possible loss or rearrangement of nonessential genes, such as the cytotoxin-hemolysin gene, can lead to a false-negative result (12).…”
mentioning
confidence: 99%